2003
DOI: 10.1203/01.pdr.0000069840.78984.76
|View full text |Cite
|
Sign up to set email alerts
|

The Nitric Oxide Synthesis Inhibitor Nω-Nitro-L-Arginine Methyl Ester (L-NAME) Causes Limb Defects in Mouse Fetuses: Protective Effect of Acute Hyperoxia

Abstract: In the present study the relationship between exposure to the nitric oxide synthesis inhibitor N -nitro-L-arginine methyl ester (L-NAME) and the induction of limb defects, with respect to stage specificity and dose dependency, was investigated in the mouse. ICR (CD-1) mice were dosed s.c with L-NAME at 50 or 90 mg/kg on gestation d 12, 13, 14, 15, or 16. A group of animals treated with vehicle on gestation d 14 served as control. Uterine contents were evaluated for teratogenesis on gestation d 18. A treatment-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…In agreement with previous observations (Tiboni and Giampietro, 2000;Tiboni et al, 2003), L-NAME failed to induce detectable signs of maternotoxicity, suggesting that alterations in maternal physiology were not involved in mediating the teratogenic action of L-NAME. Favoring the hypothesis that L-NAME acted by a direct effect on the developing conceptus is the notion that L-NAME can cross the placental barrier (Fantel et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous observations (Tiboni and Giampietro, 2000;Tiboni et al, 2003), L-NAME failed to induce detectable signs of maternotoxicity, suggesting that alterations in maternal physiology were not involved in mediating the teratogenic action of L-NAME. Favoring the hypothesis that L-NAME acted by a direct effect on the developing conceptus is the notion that L-NAME can cross the placental barrier (Fantel et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Among them, the N G -nitro-L-arginine methyl ester (L-NAME) is the agent used most frequently. Insight gained with rat (Diket et al, 1994;Pierce et al, 1995;Fantel et al, 1997Fantel et al, , 1999Fantel and Person, 2002) and mouse (Tiboni et al, 2003) models have shown that in utero exposure to L-NAME is teratogenic, causing limb reduction defects. In contrast with the majority of teratogenic agents, which act by interfering with organogenetic processes, L-NAME-mediated limb teratogenesis seems to be dependent on disruption of already developed structures.…”
Section: Introductionmentioning
confidence: 99%
“…35,41 Similar defects have been described in mice deficient in endothelial NO synthase, 36,42 but not in other NO synthase isoforms. An association between the NOS3 A922G polymorphism and orofacial clefts has been reported.…”
Section: Discussionsupporting
confidence: 65%
“…Nitric oxide has a demonstrated role in vasodilation, and genetic ablation (Gregg et al, 1998;Hefler et al, 2001;Tiboni et al, 2003) or chemical inhibition of nitric oxide synthase (Diket et al, 1994;Fantel et al, 1997Fantel et al, , 1999 produces limb defects preceded by hemorrhage, similar to what is observed following hypoxia. Almokalent and dofetilide are potassium channel-blocking drugs that have been shown in rats to produce defects associated with hemorrhage at different developmental stages including missing digits, limb defects, and tail defects (Abrahamsson et al, 1994;Danielsson et al, 1997;Webster et al, 1996).…”
Section: Hypoxia and The Edema Syndrome In Mammalian Embryosmentioning
confidence: 76%